2015
DOI: 10.1016/j.jspd.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regression Analysis of Factors Affecting Health-Related Quality of Life in Adult Spinal Deformity

Abstract: These findings reiterate the importance of patient diagnosis, age, and/or the amount of lordosis as the most important factors affecting HRQL in ASD. Gender, BMI, and sagittal vertical axis appear to be consistently important co-variables whereas coronal balance and magnitude of L curves may also be important in SRS-22. These may aid in better understanding the problem in ASD and may be useful in future classifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 20 publications
3
25
1
Order By: Relevance
“…Notably, in a study by Daubs [57] of 85 adult scoliosis patients, preoperative CSVL [ 4 cm, LC change, and sagittal imbalance (SVA) were shown to impact SRS-22 scores with the latter being the most significant predictor. In a multicenter study by Acaroglu [58] of 483 patients with adult deformity, followup coronal imbalance and LC magnitude were shown to influence SRS-22 values among the SVA, LL, BMI, gender and age. In another study by Ploumis [59] of 58 adult scoliosis patients, preoperative coronal imbalance [5 cm, LL, but not sagittal imbalance, significantly affected function and outcomes.…”
Section: Clinical Outcomesmentioning
confidence: 98%
“…Notably, in a study by Daubs [57] of 85 adult scoliosis patients, preoperative CSVL [ 4 cm, LC change, and sagittal imbalance (SVA) were shown to impact SRS-22 scores with the latter being the most significant predictor. In a multicenter study by Acaroglu [58] of 483 patients with adult deformity, followup coronal imbalance and LC magnitude were shown to influence SRS-22 values among the SVA, LL, BMI, gender and age. In another study by Ploumis [59] of 58 adult scoliosis patients, preoperative coronal imbalance [5 cm, LL, but not sagittal imbalance, significantly affected function and outcomes.…”
Section: Clinical Outcomesmentioning
confidence: 98%
“…Several authors have investigated the relationship between HRQOL and radiographic parameters. Both coronal curve location and extent were not significantly predictive of life quality in Acaroglu's study (14). Another study showed that coronal imbalance <4 cm does not influence quality of life in scoliosis (15).…”
Section: Discussionmentioning
confidence: 84%
“…In this respect, SF-36 MCS appears to be significantly different from other HRQOL parameters for which the most important governing factor had been shown to be sagittal balance and the aetiology of the deformity. 25 This being said, we may also consider that extreme cases of thoracic kyphosis may also be associated with a higher degree of pain and/or respiratory problems, both of which being factors increasing disability. Hence, the importance of thoracic kyphosis in determining the baseline SF-36 MCS may be multi-factorial, affected by appearance as well as disability of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of gender on the other hand is one that has been shown by other studies as well. 25 , 26 , 27 , 28 This is probably due to the different coping mechanisms of genders with the problems associated with ASD, be it appearance or pain and disability or both. Research consistently demonstrates that men and women differ in their responses to pain and there are multiple psychosocial processes that contribute to this difference.…”
Section: Discussionmentioning
confidence: 99%